Activating a Cu/ZnO : Al Catalyst – Much More than Reduction: Decomposition, Self‐Doping and Polymorphism. Issue 6 (28th February 2019) - Frei, Elias; Gaur, Abhijeet; Lichtenberg, Henning; Heine, Christian; Friedrich, Matthias; Greiner, Mark; Lunkenbein, Thomas; Grunwaldt, Jan‐Dierk; Schlögl, Robert
Abstract: The activation of Cu/ZnO‐based catalysts before their application is a key step and sensitive process enabling the development of the entire catalytic potential. Here, we report on a complementary (soft and hard) in‐situ X‐ray absorption spectroscopy (XAS) study investigating in detail the changes of a Cu/ZnO : Al catalyst upon thermal treatment in reducing atmosphere (10 % H2 ) at ambient pressure. The spectroscopic features of Cu, Zn and Al are investigated. Beyond the reduction event of the Cu moieties, the role of high temperature carbonate and the Al‐dopant is discussed up to the consequences for the ZnO polymorphism. The stability of the observed effects and thus their catalytic relevance are validated by operando XAS under reverse water gas‐shift conditions. Abstract : In‐situ X‐ray absorption spectroscopy (XAS) was used for investigating the changes of a Cu/ZnO : Al catalyst activated upon thermal treatment in reducing atmosphere (10 % H2 ) at ambient pressure. The stability of the observed effects and thus their catalytic relevance are validated by operando XAS under reverse water gas‐shift conditions. this combined ambient pressure in‐situ/operando XAS study reveals the importance of a proper multi‐event activation of Cu/ZnO‐based catalysts in general.